Thermal design and optimization of HIAF′s medical isotope target under extreme heat flux based on a two-way fluid–structure interaction model - Xin Li; Heng Zhang; Zihao Zhang; Jianrong Zhang; Qingfeng Tang; Wei Wang; Yucui Gao; Lei Yang; Yaling Zhang (Annals of Nuclear Energy, 2026)

U-series and OSL dating of late Pleistocene mammal fossils in Lower Pubu Cave, South China - Jiemei Zhong; Wei Liao; Yanyan Yao; Chun Tian; Guoshan Li; Qingfeng Shao; Xianjiao Ou; Wei Wang (Quaternary International, 2026)

Sustainable Fertilization in Double-Cropping Vegetable System: Evidence from A 5-Year Tomato–Brassica Campestris Field Experiment - Lijun Ren; Lili Dong; Roland Bol; Qingfeng Fan; Dan Wei; Hongtao Zou (Journal of Soil Science and Plant Nutrition, 2026)

Fish-gill-inspired hierarchical membranes with charge-repulsion-mediated ion-selective nanostructures for enhanced desalination performance - Yingxue Zhang; Wei Sun; Haoyu Jiang; Qiuxuan Zhou; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2026)

Bio-organic fertilizer regulates nutrient accumulation and microbial communities across soil aggregate in intensive vegetable production system - Lijun Ren; Lili Dong; Yanyu Han; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (Plant and Soil, 2026)

Interfacial engineering of graphene oxide with heterostructure to construct tortuous pathways in polylactic acid multilayers as barrier packaging - Qingfeng Yang; Xiaotong Sun; Dequan Zhang; Ming Tian; Wenxin Wang; Jinkai Pang; Xin Li; Wei Yang; Chengli Hou (Food Packaging and Shelf Life, 2026)

Highly efficient recovery of gold by selective sulfide reduction from chlorine leachate - Qingfeng Ling; Shiwei Zhou; Bo Li; Yonggang Wei; Hua Wang (Journal of Cleaner Production, 2026)

Synergizing early maturity and high yields through planting density and lodging-resistant strategy indica–japonica hybrid rice - Wenyu Jin; Lin Li; Qingfeng Song; Xinguang Zhu; Zhongwei Wei (Field Crops Research, 2026)

Influence of varying oxygen transmission rates in heat-shrinkable packaging on the quality of beef during 90 days of chilled storage - Ming Tian; Jintao Jia; Dequan Zhang; Xiaotong Sun; Jiarui Li; Chaoqiao Zhu; Wei Yang; Xin Li; Qingfeng Yang; Chengli Hou (Meat Science, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Impact performance of assembled aluminum alloy-concrete-carbon steel double-skin tubular column - Wengang Xu; Jigang Zhang; Qingfeng Yan; Wenli Chen; Zaixian Chen; Wei Li; Yun Niu; Zhaolong Li (Ocean Engineering, 2026)

Bio-organic fertilization promotes soil nutrient cycling and reduces CO2 emissions via regulating bacterial communities in vegetable production system - Lijun Ren; Lili Dong; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (European Journal of Soil Biology, 2026)

Ecological responses of the largest lake-wetland system (North China Plain) to hydrological regulation and cultural eutrophication over the past 70 years - Longjuan Cheng; John P. Smol; Qi Lin; Chaoran Wei; Shuyi Yang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Bin Xue (Anthropocene, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Experimental and numerical study on ice-induced vibration control of jacket-type offshore wind turbine using tuned mass damper - Rui Wang; Jigang Zhang; Zhehao Ma; Qingfeng Yan; Feifei Liu; Zaixian Chen; Wei Li; Yun Niu (Ocean Engineering, 2026)

Integrated Analysis of Phenotypic and Hepatic Transcriptomic Profiles Reveals Enhanced Cold Tolerance in Triploid Crucian Carp - Suifei Tao; Zexun Zhou; Shandong Chen; Jialin Cui; Yude Wang; Kaikun Luo; Wei Liu; Qingfeng Liu; Wuhui Li; Shaojun Liu (Fishes, 2025)
Cold stress poses a critical threat to fish survival by triggering metabolic dysfunction, oxidative damage, immune suppression, and apoptosis. However, hybrid polyploid fish triploid crucian carp (3nRCR, 3n = 150) demonstrate superior stress tolerance. In this study, we investigated the cold adaptation mechanisms in different ploidy cyprinid fishes: triploid crucian carp compared to its diploid improved red crucian carp (Carassius auratus red var., RCC, 2n = 100, ♀) and improved allotetraploid (4nAT, 4n = 200, ♂) progenitors. Under controlled cooling, 3nRCR lost equilibrium at a significantly lower temperature (3.2 °C) than RCC (4.0 °C) and 4nAT (4.5 °C), confirming its superior enhanced cold resistance. Histological examination revealed minimal tissue damage in 3nRCR, characterized by reduced gill inflammation and cellular apoptosis. Transcriptomics revealed triploid-specific molecular strategies: 3nRCR uniquely activated retinol metabolism and metabolic rewiring (arginine/proline metabolism, oxidative phosphorylation). Notably, in the immune-related NLR signaling pathway, both nlrp1 and nlrp3 (key inflammasome components) were significantly downregulated in 3nRCR (p

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Bacillus subtilis morphology and bentonite colloids govern Eu(III) transport in quartz sand: Mechanisms and machine learning insights - Qingfeng Tang; Zhengye Feng; Yanhui Wang; Xiaoyan Wei; Duoqiang Pan; Wangsuo Wu; Zhen Xu (Journal of Hazardous Materials, 2025)

Conservation and divergence of OsGSTU9 and OsGSTU19 in cadmium detoxification and accumulation in rice - Xuan Chen; Wei Jiang; Di Chang; Qingfeng Zheng; Chunmeng Zhu; Li Hao; Fanrong Zeng; Zhong-Hua Chen; Guang Chen; Yuan Qin; Fenglin Deng (Journal of Hazardous Materials, 2025)

Persistently centennial to millennial variability of Asian summer monsoon and north-south coupling during the late penultimate glacial period - Wei Huang; Zhenqiu Zhang; Kan Zhao; Yongjin Wang; Qingfeng Shao; Jinguo Dong; Xiuyang Jiang; Xiumin Zhai; Carlos Pérez-Mejías (Global and Planetary Change, 2025)

Sb3+-doped terbium-based metal halide with efficient dual band emission for ratiometric temperature sensing - Zhe Tang; Xiaochen Wang; Shuyue Wang; Maria Syskaki; Qingfeng Wei; Binbin Fan; Chenxin Fan; Dandan Luo; Tianxin Bai; Junsheng Chen (Chemical Engineering Journal, 2025)

Electrospinning-mist polymerized antibacterial and super-hydrophilic nanofiber membrane for efficient dust filtration and enhanced comfort in mines - Gang Zhou; Liwei Jiang; Bo Wei; Pengjin Liu; Jiafa Du; Tingting Fan; Song Xin; Rulin Liu; Qingfeng Xu; Seeram Ramakrishna (Chemical Engineering Journal, 2025)

Predicting CircRNA-Disease Associations Based on Heterogeneous Graph Neural Network and Knowledge Graph Attribute Mining Attention - Wei Lan; Cong Peng; Hongyu Zhang; Chunling Li; Qingfeng Chen; Xin Xiao; Zhiqiang Wang (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Vibration damping and finite element analysis of a 10 MW jacket-type offshore wind turbine - Jigang Zhang; Haodong Sui; Zhehao Ma; Wenli Chen; Qingfeng Yan; Wei Li; Hongjian Xu; Fengbo Yu; Yun Niu; Junxian Zhao (Ocean Engineering, 2025)

Microbially mediated mechanisms underlie N2O mitigation by bio-organic fertilizer in greenhouse vegetable production system - Lijun Ren; Lili Dong; Guopeng Liang; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (Applied Soil Ecology, 2025)

Sustainable nanofiber films based on polylactic acid/modified cellulose nanocrystals containing various types of polyphenols, exhibiting antioxidant activity and high stability - Chaoqiao Zhu; Qingfeng Yang; Ming Tian; Wei Yang; Chengjun Min; Simin Fan; Debao Wang; Xin Li; Dequan Zhang; Chengli Hou (Food Chemistry, 2025)

Effects of dietary rumen-degradable protein on the growth performance, energy, and nitrogen metabolism of dairy buffalo heifers - Qingfeng Tang; Pengcheng Shao; Chongli Wen; Zeming Bu; Guangsheng Qin; Yali Huang; Yuhong Pan; Zhipei Li; Kelong Wei; Shulu Li; Bishi Lan; Huapei Zhong; et al. (Tropical Animal Health and Production, 2025)

Predicting the Concentrations of Rare Earth Elements and Yttrium in Coal Using Self-Organizing Map - Na Xu; Fei Li; Wei Zhu; Mark A. Engle; Jiapei Kong; Pengfei Li; Qingfeng Wang; Lishan Shen; Robert B. Finkelman; Shifeng Dai (Natural Resources Research, 2025)

Knowledge graphs analysis for research on minerals in coal - Pengfei Li; Na Xu; Qingfeng Wang; Yuqing Wang; Fei Li; Wei Zhu; Qing Li (Earth Science Informatics, 2025)

Optimizing landslide susceptibility mapping using integrated forest by penalizing attributes model with ensemble algorithms - Wei Chen; Chao Wang; Xia Zhao; Li Bai; Qingfeng He; Xi Chen; Qifei Zhao; Ruixin Zhao; Tao Li; Paraskevas Tsangaratos; Ioanna Ilia (Earth Science Informatics, 2025)

Enhancement of the flavor compound 3-Methylbutanal and sensory quality in sausages fermented by Lactococcus lactis CGMCC 31087: Leucine and α-Ketoglutaric acid as supplements - Lei Chen; Congjiao Wei; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Food Chemistry, 2025)

Mechanistic model for the cotransport of colloids and radionuclides in saturated porous systems based on the interaction forces between colloids - Qi Tan; Qingfeng Tang; Xinyi Shi; Hongjie Zhao; Shuyang Li; Yuan Chen; Xiaoyan Wei; Zhen Xu; Duoqiang Pan; Wangsuo Wu (Applied Geochemistry, 2025)

The impact of sub-pixel scale urban function on urban heat island: Insights derived from its decomposition - Qingfeng Guan; Yajun Li; Wenjia Huang; Wei Cao; Zhewei Liang; Jie He; Xun Liang (Applied Geography, 2025)

Structural performance and design of assembled aluminum alloy-concrete-carbon steel double-skin tubular column - Wengang Xu; Jigang Zhang; Qingfeng Yan; Wei Li; Zhenhui Song; Fengbo Yu; Yun Niu; Hanyu Song (Ocean Engineering, 2025)

Microbial community and dynamic changes of extracellular polymeric substances in relation to plastisphere of disposable surgical masks in natural aquatic environment - Ling Zhang; Yuxin Zhou; Zixian Zhu; Feifei Yan; Luxi Tan; Chunyan Wei; Zihao Wang; Qingfeng Chen; Ying Zhang (Journal of Oceanology and Limnology, 2025)

Intelligent identification of coal macerals using improved semi-supervised semantic segmentation methods - Na Xu; Qingfeng Wang; Pengfei Li; Jiapei Kong; Qing Li; Mark A. Engle; James C. Hower; Wei Zhu (International Journal of Coal Geology, 2025)

Diversity and conservation of medicinal plants in tropical East Africa - Shenglan Du; Maxwell Njoroge Njenga; Yuvenalis Morara Mbuni; Muchuku John Kamau; Neng Wei; Robert Wahiti Gituru; Geoffrey Mwachala; Beth A. Kaplin; Shengwei Wang; Qingfeng Wang (Biodiversity and Conservation, 2025)

Enhancement of calcium alginate and urea in gel-modified dry water inhibition of methane-air explosion - Qiuhong Wang; Bin Peng; Jun Deng; Wei Gao; Chao Ma; Qingfeng Wang; Youjie Sheng; Dong Zhao (Process Safety and Environmental Protection, 2025)

Incorporating graphene quantum dots boosts thermoelectric performance of PEDOT:PSS films - Ting Wu; Xiao-Lei Shi; Yu-Yu Deng; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Fang Yue; Pei Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2025)

High-performance thermoelectric PEDOT:PSS fiber bundles via rational ionic liquid treatment - Yu-Yu Deng; Xiao-Lei Shi; Ting Wu; Hao Wu; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Pei Huang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Anti-enterovirus 71 activity of native fucosylated chondroitin sulfates and their derivatives - Qingfeng Niu; Han Zhou; Xiaoyao Ma; Yuanyuan Jiang; Chanjuan Liu; Wei Wang; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2024)

Gckr depletion leads to growth retardation and diet-dependent visceral obesity in red crucian carp (Carassius auratus red var.) - Juan Li; Huilin Li; Yuan Ou; Qiyong Lou; Zehong Wei; Ming Wen; Shi Wang; Qingfeng Liu; Yuqin Shu; Shaojun Liu (Aquaculture, 2024)

Unlocking maize yield potential through exploring canopy-root interactions with nature-based nutrient management - Yupeng Zhu; Junhao Wang; Yongjun Zhu; Han Lai; Ziren Qu; Jian Zhao; Dan Wei; Pu Wang; Qingfeng Meng (Field Crops Research, 2024)

Cr(VI) behaves differently than Cr(III) in the uptake, translocation and detoxification in rice roots - Adeel Riaz; Yuan Qin; Qingfeng Zheng; Xuan Chen; Wei Jiang; Bisma Riaz; Nayun Xiao; Xiaojian Wu; Xianjin Qiu; Jianlong Xu; Guang Chen; Zhong-Hua Chen; et al. (Science of The Total Environment, 2024)

Water stress combining weather condition shapes wheat yield and inter-annual yield variability: Field observations from a six-year study - Dan Wei; Beijing Tian; Qingzhao Wu; Haijiang Wang; Pu Wang; Qingfeng Meng (European Journal of Agronomy, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Pure salt expansion behavior in sulfate saline soil under negative temperature conditions - Fengling Ji; Yuansheng Peng; Qingfeng Lv; Wei Li; Jingjing Yu (Cold Regions Science and Technology, 2024)

Spatiotemporal response of the optical characteristics of dissolved organic matter to seasonality and land use in tropical island rivers - Yaxin Xiao; Chaoxian Wei; Qingfeng Wang; Ying Shan; Guiliang Wang; Jinchuang Wang (Environmental Geochemistry and Health, 2024)

Effects of different cold chain logistics modes on the quality and bacterial community succession of fresh pork - Su Wang; Dequan Zhang; Qingfeng Yang; Xiangyuan Wen; Xin Li; Tongjing Yan; Rui Zhang; Wei Wang; Kumayl Hassan Akhtar; Caiyan Huang; Chengli Hou (Meat Science, 2024)

Zein and tannic acid hybrid particles improving physical stability, controlled release properties, and antimicrobial activity of cinnamon essential oil loaded Pickering emulsions - Simin Fan; Qingfeng Yang; Debao Wang; Chaoqiao Zhu; Xiangyuan Wen; Xin Li; Aurore Richel; Marie-Laure Fauconnier; Wei Yang; Chengli Hou; Dequan Zhang (Food Chemistry, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Contribution of mono- and co-culture of Pseudomonas paralactis, Acinetobacter MN21 and Stenotrophomonas maltophilia to the spoilage of chill-stored lamb - Xiangyuan Wen; Dequan Zhang; James D. Morton; Su Wang; Xiaoyu Chai; Xin Li; Qingfeng Yang; Jinhuo Li; Wei Yang; Chengli Hou (Food Research International, 2024)

Forces driving ecological degradation in southern China during the MIS3: Natural or anthropogenic? - Qiong Chen; Xiaobo Huang; Hua Tu; Qingfeng Shao; Xiaoming Sun; Qiaofen Liu; Wei Wang; Zhongping Lai; Xiaoqiang Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Evidence for the smallest fossil Pongo in southern China - Hua Liang; Terry Harrison; Qingfeng Shao; Jean-Jacques Bahain; Jinyou Mo; Yuexing Feng; Wei Liao; Wei Wang (Journal of Human Evolution, 2024)

Benthic foraminiferal assemblages in the coastal zone of the yellow river delta: Environmental significance and characteristics of microbial diversity - Shuyang Huang; Qing Li; Xiaohua Qiu; Hong You; Ruimin Lv; Wei Liu; Qingfeng Chen; Tiantian Wang; Jing Zhang; Junjian Ma; Zihao Wang; Shigang Ding (Continental Shelf Research, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Can high-yielding maize system decrease greenhouse gas emissions largely while simultaneously enhancing economic and ecosystem benefits through the “Rhizobiont” concept? Evidence from field - Yupeng Zhu; Ziren Qu; Jian Zhao; Junhao Wang; Dan Wei; Qingfeng Meng (Science of The Total Environment, 2024)

Multifunctional chemoreactive nanosonosensitizers exert antitumoral, antibacterial and wound healing effects on malignant peripheral nerve sheath tumors - Wei Wang; Yaling Zheng; Haibo Li; Chengjiang Wei; Luodan Yu; Yihui Gu; Qingfeng Li; Yu Chen; Zhichao Wang (Chemical Engineering Journal, 2023)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

The hind information: Exploring the impact of physical damage on mask microbial composition in the aquatic environment - Hu Wang; Zixian Zhu; Ling Zhang; Xiaohui Liu; Weihong Sun; Feifei Yan; Yuxin Zhou; Zhi Wang; Xiaofeng Wang; Chunyan Wei; Jie Lai; Qingfeng Chen; et al. (Environmental Research, 2023)

Spatial pattern and cause of centennial-scale hydroclimatic variability over eastern China during the last millennium - Jian-Jun Yin; Zhijun Wang; Wenqiang Shi; Qingfeng Shao; Xia Wu; Wei Tang; Yuan Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Enhancing maize yield through understanding the novel shoot-root interaction in morphology among hybrids with dense planting - Yupeng Zhu; Su Wang; Yunhao Li; Dan Wei; Ning Luo; Pu Wang; Qingfeng Meng (Field Crops Research, 2023)

Diverse water management in a preceding wheat crop does not affect maize yield but increases inter-annual variability: A six-year field study - Dan Wei; Ning Luo; Yupeng Zhu; Pu Wang; Qingfeng Meng (Field Crops Research, 2023)

The impact of ambient air pollutants on childhood respiratory system disease and the resulting disease burden: a time-series study - Wenbin Shen; Xue Li; Qingfeng Fang; Guoao Li; Wei Xiao; Yueyang Wu; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (International Archives of Occupational and Environmental Health, 2023)

Interannual variation in gross ecosystem production and evapotranspiration in a temperate semiarid grassland undergoing vegetation recovery - Xinhao Li; Tianshan Zha; Peng Liu; Charles P.-A. Bourque; Xin Jia; Yun Tian; Chuan Jin; Xiaoshuai Wei; Xinyue Liu; Hongxian Zhao; Qingfeng Xu; Shaorong Hao (Agricultural and Forest Meteorology, 2023)

Pyrite and sulfur-coupled autotrophic denitrification system for efficient nitrate and phosphate removal - Xuzhen Liu; Changsheng Zhao; Tongtong Xu; Wei Liu; Qingfeng Chen; Luzhen Li; Yu Tan; Xiaokai Wang; Yanan Dong (Bioresource Technology, 2023)

Ordered macroporous carbonous skeletons implanted with dual-phase Co/CoFe nanoparticles for boosting electrocatalytic performance - Jun-Xuan Li; Longlong Fan; Qingfeng Hua; Qinghong Geng; Yingying Zhang; Xiaoli Fan; Lian Ma; Chengming Wang; Wei Zhu; Xiao Feng; Cuiling Li (Chemical Engineering Journal, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Highly enhanced direct catalytic oxidation of cyclohexane to adipic acid with molecular oxygen: Dynamic collaboration between zeolite channel micro-environment and Au clusters - Zhiyang Zhang; Mi Hu; Qingfeng Gui; Jing Gu; Wenlong Xu; Qingbo Xiao; Wei Huang (Chemical Engineering Journal, 2023)

Middle Pleistocene Pongo from Ganxian Cave in southern China with implications for understanding dental size evolution in orangutans - Hua Liang; Terry Harrison; Qingfeng Shao; Jean-Jacques Bahain; Jianxin Zhao; Christopher J. Bae; Wei Liao; Wei Wang (Journal of Human Evolution, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Alleviating groundwater depletion while realizing food security for sustainable development - Dan Wei; Xinglong Wang; Ning Luo; Yupeng Zhu; Pu Wang; Qingfeng Meng (Journal of Cleaner Production, 2023)

New remains of Ailuropoda melanoleuca baconi from Yanjinggou, China: Throwing light on the evolution of giant pandas during the Pleistocene - Haiqian Hu; Haowen Tong; Qingfeng Shao; Guangbiao Wei; Haidong Yu; Jingsong Shi; Xunqian Wang; Can Xiong; Yu Lin; Ning Li; Zhaoying Wei; Ping Wang; et al. (Journal of Mammalian Evolution, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

Design, synthesis and biological evaluation of Schiff’s base derivatives as multifunctional agents for the treatment of Alzheimer’s disease - Jian Shi; Yi Zhou; Keren Wang; Qinge Ma; Rongrui Wei; Qingfeng Li; Yiyang Zhao; Zhanpin Qiao; Shuang Liu; Yumin Leng; Wenmin Liu; Zhipei Sang (Medicinal Chemistry Research, 2021)

Associations of MMP-2 −1306 C/T and MMP-9 −1562 C/T polymorphisms with breast cancer risk among different populations: a meta-analysis - Meng Han; Qingfeng Yang; Kai Feng; Rongping Li; Jia Ren; Liguang Wei (Genes & Genomics, 2017)

Sulfur- and lead-isotope geochemistry of the Balugou Cu-Pb-Zn skarn deposit in the Wulonggou area in the eastern Kunlun Orogen, NW China - Qingfeng Ding; Wei Yan; Benlong Zhang (Journal of Earth Science, 2016)

Effect of mevalonic acid on cholesterol synthesis in bovine intramuscular and subcutaneous adipocytes - Xiaomu Liu; Wei You; Haijian Cheng; Qingfeng Zhang; Enliang Song; Fachun Wan; Hong Han; Guifen Liu (Journal of Applied Genetics, 2016)

Distribution of carbon and nitrogen in water-stable aggregates and soil stability under long-term manure application in solonetzic soils of the Songnen plain, northeast China - Qingfeng Meng; Yuting Sun; Jing Zhao; Lianren Zhou; Xianfa Ma; Meng Zhou; Wei Gao; Guangcheng Wang (Journal of Soils and Sediments, 2014)

Diversity of Gene Cassette Promoter Variants of Class 1 Integrons in Uropathogenic Escherichia coli - Quhao Wei; Xiaofei Jiang; Min Li; Gang Li; Qingfeng Hu; Huoxiang Lu; Guoqiang Chen; Yonglie Zhou; Yuan Lu (Current Microbiology, 2013)

The Expression Patterns of Septin-9 After Traumatic Brain Injury in Rat Brain - Hui Mao; Jiao Liu; Wei Shi; Qingfeng Huang; Xide Xu; Lanchun Ni; Feihui Zou; Jinlong Shi; Debao Li; Yonghua Liu; Jian Chen (Journal of Molecular Neuroscience, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)